Mulheres negras no palco do debate sobre crimes raciais: uma análise das ofensas racistas no Tribunal de Justiça do Pará - SIQUEIRA, Samara Tirza Dias (Universidade Federal do Pará, 2023)
In this research, I will investigate the violence imposed on women in the racist insults present in the judgments of the Court of Justice of Pará, published between the years 2009 and 2020. For that, I will analyze the racial composition of the Court, the racist offenses judged in the judgments studied and norms for combating gender-based and racial violence. As a methodology, I will use the inductive and colored method. In addition, I will use jurisprudential, documentary, bibliographic research and content analysis of the selected decisions. First, I will address the Court’s racial profile, based on information from the census carried out by the National Council of Justice (CNJ, 2018), in the light of studies on whiteness, reflecting on the absence of black women in the judiciary. In a second moment, I will classify the offenses examined into categories, with the aim of verifying the violence that influences racist insults against black women. Finally, I will explain about the invisibility of black women in studies about the criminalization of racism, as well as in the elaboration of policies to combat gender violence and racial violence. In the end, I realized that black women suffer a specific victimization process in the context of racial crimes. Furthermore, there is a need to recognize their suffering and consider them as autonomous subjects in the discussions and in the creation of policies to combat racial violence and gender violence, at the risk of perpetuating violations, excluding them from the scope of protection. of the created measures.